Assessment of the Dynamic Alteration of Choriocapillaris Vessel Density after Focal Laser Photocoagulation with OCT Angiography - Zuohuizi Yi; Yiqiao Xing; Changzheng Chen; Xiaoling Wang; Juejun Liu; Lu He; Hongmei Zheng (Journal of Ophthalmology)
Purpose. To evaluate the changes of choriocapillaris blood flow beneath laser lesions in noncenter-involved diabetic macular edema patients using optical coherence tomography angiography (OCTA). Methods. This was a retrospective case-series study. We used OCTA to analyze the characteristics of the choriocapillaris blood flow beneath laser lesions before laser treatment and at several intervals after treatment. The choriocapillaris vessel density (CCVD) beneath the laser lesions was based on the OCTA images and was defined as the proportion of flow pixels in the selected area calculated using FIJI software through automatic binarization processing based on threshold methods. Results. A total of 63 laser lesions in 8 eyes of 5 patients were included in this study. There was a significant decrease in the CCVD at 1 hour and 1 day following laser treatment (24.25% ± 5.04% and 22.00% ± 4.71%, respectively) when compared with the baseline value (39.09% ± 3.71%, all p<0.001). The CCVD was 31.82% ± 4.53% in 1 week after laser treatment, which was significantly higher than that in 1 day after treatment (p<0.001), and then continued to improve at 1 month after treatment (34.44% ± 4.16%). Additionally, in the group with smaller spot size and lower energy, the CCVD recovery at 1 month after laser was significantly better than that in the group with larger spot size and higher energy (p=0.006). Conclusions. OCTA image analysis can reflect changes in the choriocapillaris blood flow beneath laser lesions at different times following laser treatment in vivo. Spot size and laser energy may affect blood flow recovery.